Regular, low-dose methadone for reducing breathlessness in people experiencing or at risk of neurotoxic effects from morphine: A single-center case series - Sobanski, Piotr Z.; Currow, David C. (Frontiers in Medicine, 2022)
Breathlessness is a common symptom suffered by people living with advanced malignant and non-malignant diseases, one which significantly limits their quality of life. If it emerges at minimal exertion, despite the maximal, guidelines-directed, disease-specific therapies, it should be considered persistent and obliges clinicians to prescribe symptomatic, non-pharmacological, and pharmacological treatment to alleviate it. Opioids are recommended for the symptomatic treatment of persistent breathlessness, with morphine most extensively studied for this indication. It is extensively metabolized in the liver into water-soluble 3- and 6-glucuronides, excreted by the kidneys. In the case of advanced renal failure, the glucuronides accumulate, mainly responsible for toxicity 3-glucuronides. Some people, predominantly those with advanced renal failure, develop neurotoxic effects after chronic morphine, even when prescribed at a very low dose. A single-center case series of consecutive patients experiencing neurotoxic effects after long-term, low-dose morphine or at risk of such effects were transferred to methadone to avoid the accumulation of neurotoxic metabolites. Over the course of 4.5 years, 26 patients have been treated with methadone in the median dose of 3.0 mg/24 h p.o., for persisting breathlessness. Sixteen of them had been treated previously with an opioid (usually morphine) at the median dose of 7.0 mg/24 h (morphine oral daily dose equivalent). They were transferred to methadone, with the median dose of 3.0 mg/24 h orally (methadone oral daily dose equivalent), and the median morphine-to-methadone dose ratio was 2.5:1. All patients experienced a meaningful improvement in breathlessness intensity after methadone, by a median of 5 points (range 1–8) on the 0–10 numerical rating scale (NRS) in the whole group, and by 2 points (range 0–8) in those pretreated with other opioids, mainly morphine. Low-dose methadone can be considered an efficient alternative to morphine for reducing breathlessness in people experiencing neurotoxic effects or at risk of developing them following treatment with morphine.